How the Use of Fees, Fines and Bail Have Been Used to Criminalize Poverty: Can Reforms Help Put the Genie Back in the Bottle? - Heller, Thomas Allan (Collected Papers of Thomas A. Heller, 2025)
The rallying cry of many American politicians is Law and Order. This tactic wins votes. As a result of its Wars on Crime, Drugs, and the Impoverished, America has the highest rate of incarceration in the world. This article explores how, over the past few decades, politicians have charged criminal defendants every imaginable fee and fine as they wind their way through the criminal justice system in order to fund the massive prison complex that the politicians do not want to tax Americans for. These tactics have criminalized poverty, as they disproportionately impact the most marginalized in American society. These abusive and unfair tactics have drawn scrutiny from policymakers in recent years, including the American Bar Association, which adopted stringent guidelines to help inform policymakers of this critical problem in an effort to reign in the abusive use of fees and fines. The paper discusses recent reforms, many at the urging of the Department of Justice, Office for Access to Justice, in conjunction with the ABA. It discusses the main Supreme Court cases that considered the Excessive Fines Clause of the Eighth Amendment.